The bulk modulus of β-type Titanium Alloys for Hip and Bone Replacement - Adnan Mahmood Khalid (Tikrit Journal of Pure Science, 2023)
Although aluminum (Al) and vanadium (V) have been shown to be cytotoxic, titanium and its Ti-6AI4V alloy have been utilised extensively as implant materials for many years. This is due to new titanium alloys consisting of non-cytotoxic substances like molybdenum (Mo), tantalum (Ta), niobium (Nb), zirconium (Zr), or tin (Sn) have advanced when treated as a cubic β-phase alloy, which has led to the investigation of Al and V free titanium alloys. When configured as a cubic β-phase alloy, they exhibit abnormal corrosion resistance as well as decreased elasticity moduli that are comparable to the substance of the bone they are repairing.